2010
DOI: 10.1016/j.bbamcr.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Jagged/Notch signalling is required for a subset of TGFβ1 responses in human kidney epithelial cells

Abstract: The Jagged/Notch pathway has been implicated in TGFβ1 responses in epithelial cells in diabetic nephropathy and other fibrotic conditions in vivo. Here, we identify that Jagged/Notch signalling is required for a subset of TGFβ1-stimulated gene responses in human kidney epithelial cells in vitro. TGFβ1 treatment of HK-2 and RPTEC cells for 24h increased Jagged1 (a Notch ligand) and Hes1 (a Notch target) mRNA. This response was inhibited by co-incubation with Compound E, an inhibitor of γ-secretase (GSI), an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 46 publications
6
53
0
Order By: Relevance
“…Other intracellular pathways and transcription factors such as Erk-1/2 and Wnt signalling are also thought to be involved in mediating EMT (Schramek et al 2003;Taki et al 2003). The Jagged/Notch signalling pathway has recently been implicated as an important regulator of EMT and renal fibrosis (Leask 2010;Nyhan et al 2010;Zavadil et al 2004) and Jagged/Notch-mediated EMT is associated with increased expression of Snail (Saad et al 2010). Future experiments will delineate whether any of these pathways can be targeted specifically for the treatment and prevention of renal fibrosis.…”
Section: Signalling Pathways Involved In Emtmentioning
confidence: 96%
“…Other intracellular pathways and transcription factors such as Erk-1/2 and Wnt signalling are also thought to be involved in mediating EMT (Schramek et al 2003;Taki et al 2003). The Jagged/Notch signalling pathway has recently been implicated as an important regulator of EMT and renal fibrosis (Leask 2010;Nyhan et al 2010;Zavadil et al 2004) and Jagged/Notch-mediated EMT is associated with increased expression of Snail (Saad et al 2010). Future experiments will delineate whether any of these pathways can be targeted specifically for the treatment and prevention of renal fibrosis.…”
Section: Signalling Pathways Involved In Emtmentioning
confidence: 96%
“…Using proximal tubule cell line models, HK2 and RPTEC cells, they demonstrated that the Jagged/Notch signalling pathway is activated in response to TGF-β1. Furthermore, the cytokine-evoked changes in Jagged 1 expression preceeded EMT associated gene changes in both E-cadherin and vimentin, effects which appeared to be dependent on Smad3 activity [36]. Therefore, TGF-β1 can modulate transcription of multiple target genes through the activation of at least one, or a cross talk of multiple signaling pathways.…”
mentioning
confidence: 96%
“…This process leads to increased myofibroblast accumulation and scarring11. Recent evidence has shown that the Notch signaling pathway promotes EMT via interactions with the TGF-β signaling pathway in the kidney tubular epithelium20.…”
Section: Discussionmentioning
confidence: 99%